Social evaluative implications of sensory adaptation to human voices - Kelsey L. Neuenswander; Grace S. R. Gillespie; David J. Lick; Gregory A. Bryant; Kerri L. Johnson (Royal Society Open Science, 2024)
People form social evaluations of others following brief exposure to their voices, and these impressions are calibrated based on recent perceptual experience. Participants adapted to voices with fundamental frequency (f o; the acoustic correlate of perceptual pitch) manipulated to be gender-typical (i.e. masculine men and feminine women) or gender-atypical (i.e. feminine men and masculine women) before evaluating unaltered test voices within the same sex. Adaptation resulted in contrastive aftereffects. Listening to gender-atypical voices caused female voices to sound more feminine and attractive (Study 1) and male voices to sound more masculine and attractive (Study 2). Studies 3a and 3b tested whether adaptation occurred on a conceptual or perceptual level, respectively. In Study 3a, perceivers adapted to gender-typical or gender-atypical voices for both men and women (i.e. adaptors pitch manipulated in opposite directions for men and women) before evaluating unaltered test voices. Findings showed weak evidence that evaluations differed between conditions. In Study 3b, perceivers adapted to masculinized or feminized voices for both men and women (i.e. adaptors pitch manipulated in the same direction for men and women) before evaluating unaltered test voices. In the feminized condition, participants rated male targets as more masculine and attractive. Conversely, in the masculinized condition, participants rated female targets as more feminine and attractive. Voices appear to be evaluated according to gender norms that are updated based on perceptual experience as well as conceptual knowledge.